Asymptotic Behavior and Stationary Distribution of a Nonlinear Stochastic Epidemic Model with Relapse and Cure. (1st August 2020) - Ma, Jiying; Yi, Qing
Abstract : In this paper, by introducing environmental perturbation, we extend an epidemic model with graded cure, relapse, and nonlinear incidence rate from a deterministic framework to a stochastic differential one. The existence and uniqueness of positive solution for the stochastic system is verified. Using the Lyapunov function method, we estimate the distance between stochastic solutions and the corresponding deterministic system in the time mean sense. Under some acceptable conditions, the solution of the stochastic system oscillates in the vicinity of the disease-free equilibrium if the basic reproductive number R 0 ≤ 1, while the random solution oscillates near the endemic equilibrium, and the system has a unique stationary distribution if R 0 > 1 . Moreover, numerical simulation is conducted to support our theoretical results.